If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11x-37=6(x+33)
We move all terms to the left:
11x-37-(6(x+33))=0
We calculate terms in parentheses: -(6(x+33)), so:We get rid of parentheses
6(x+33)
We multiply parentheses
6x+198
Back to the equation:
-(6x+198)
11x-6x-198-37=0
We add all the numbers together, and all the variables
5x-235=0
We move all terms containing x to the left, all other terms to the right
5x=235
x=235/5
x=47
| 7-3a+8=9 | | 3x^2-80x+1400=0 | | 4x-38=x | | 15w-7w+1=17 | | 20t−19t−1=8 | | -6x-32=8x+32 | | (5x+3)(x+3)=0 | | 1/6n+15=18 | | -2x+200=6x | | -5x+3=x+9 | | (x-2)7=56 | | 9n-n=4 | | -2x7=56 | | 5m=0,5 | | 1,3x-7,43=1,5/(2,5-2x) | | 3x+4=2x+21 | | 7x-(4x-12)=36 | | -2r-5r=-14 | | -8=t=-12 | | 1,3x-7,43=1,5x(2,5-2x) | | 25d=250 | | 1,3x-7,43=1,5•(2,5-2x) | | 9=x÷2 | | -59-x=-11x+91 | | h(17+2)=1/2 | | x-2.94=4.4 | | 4x-33=x+12 | | 8x-13=5x+20 | | 3.2x=2.6=-23 | | x=5x+4+2x+9+x+15 | | 9-5x=3x-7 | | 4a-2a=7+17 |